Integrated glycerol biorefinery: volatile fatty acid platform for polyhydroxyalkanoates production under feast/famine operation - Agnes Adam Duarte Pinheiro; Edilberto Mariano da Silva; Bruna Scandolara Magnus; Federico Battista; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Bioresource Technology, 2026)

Sustainable phosphorus capture with PZsorb: Reducing pollution and enabling circular nutrient management - Mariam Darestani; Bijan P. Markhali; Adam Farahani; Matheus C. Duarte; Atefeh Ahmadbeigi; Deshveen Chandran; Ricky-John Spencer; David E.J. Garman; Pooja Kaur Chaggar; Kazem Javan (Journal of Water Process Engineering, 2026)

Insights into volatile fatty acid production and fermentation pathways of microalgae biomass combined with vinasse and glycerol - Dicla Cesário Pereira de Oliveira; Francyelle Karolynne Vieira Machado; Agnes Adam Duarte Pinheiro; Federico Battista; Mario Takayuki Kato; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Environmental Science and Pollution Research, 2026)
The fermentation of industrial wastes derived from water recovery (pretreated microalgae biomass, PTMB), biodiesel (glycerol, GLY), and ethanol (vinasse, VIN)) is a promising sustainable alternative for producing volatile fatty acids (VFA). In this study, controlled fermentation experiments were performed using PTMB-VIN and PTMB-GLY mixtures with varying substrate concentrations and retention times to optimize the VFA yield and production efficiency. Acid fermentation was optimized at a 3-day hydraulic retention time, and methanogenic reactions were enhanced at longer hydraulic retention times. Increasing the organic loading rate resulted in a high VFA yield (13.10 g VFA-COD . L −1 ) and a conversion rate of approximately 40%. GLY fermentation followed the oxidative and reductive pathways at a balanced redox potential. PTMB is linked to the oxidative pathway, and GLY is involved in the reductive pathway. Tests with PTMB-GLY resulted in limiting conditions, but significant observations regarding the metabolic pathway and the effect of PTMB were made.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Staying hooked: effective science engagement and communication in recreational fisheries - Pablo Pita; Sean Tracey; Robert Arlinghaus; Eneko Bachiller; Filipa Pinho-Duarte; Keno Ferter; Filipe Henriques; Samantha Hook; Kieran Hyder; Alejo Irigoyen; María P. Jiménez; Martín Laporta; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries. ● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions. ● Public involvement and stakeholder engagement are essential for effective management. ● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding. ● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks. ● Funding for communication efforts is often insufficient but remains crucial for success. ● Participatory workshops and data-sharing arrangements enhance collaboration and involvement. ● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Invisible Hand of Sampling for Management: Underlying Needs to Survey a Threatened Seabird Can Bias Aggregated Data - Ryan Baumbusch; Adam Duarte; James T. Peterson (Journal of Biogeography, 2025)
Aim Surveying for a species of concern ahead of proposed activities that alter its habitat is routine practice in conservation and management. Such surveys may accumulate large datasets that could further elucidate trends in abundance and distribution. However, the as‐needed surveying of proposed activities may impart a sample site selection bias on the data if used for another purpose. Management of a threatened, forest‐nesting seabird offered an example of this. Here we assessed how resource management planning and survey requirements can bias clearance monitoring survey data collected prior to proposed timber harvests, if those data are used for other purposes. Location Oregon and Washington, USA. Taxon Marbled Murrelet ( Brachyramphus marmoratus ). Methods To assess how timber planning and other factors influenced marbled murrelet survey location selection, we used logistic regression models to examine habitat associations of marbled murrelet survey sites ( n = 9178) encompassing proposed timber harvests, and the survey stations ( n = 38,923) therein, across the murrelet's inland range in Washington and Oregon, USA between 1989 and 2021. We then simulated the effect this selective sampling might have on assessments of occupancy trends. Results Most habitat characteristics considered did influence where surveys were located, with distance to roads often being the strongest predictor of survey location. The strength of selection for each covariate changed over time, such that a habitat characteristic strongly influenced location selection in a year but was less influential in another year. The simulation analysis suggested that the non‐random selection of survey sites could profoundly bias assessments of occupancy trends. Conclusions When using these clearance monitoring survey data– or any data–beyond their original purpose, careful consideration should be given to the scope of inference provided and analytical methods used, to ensure that observed trends are the product of biological processes and not biased by sampling artefacts.

Bayesian networks facilitate updating of species distribution and habitat suitability models - Adam Duarte; Robert S. Spaan; James T. Peterson; Christopher A. Pearl; Michael J. Adams (Ecological Modelling, 2025)

An integrated analysis for estimation of survival, growth, and movement of unmarked juvenile anadromous fish - Patti J. Wohner; Adam Duarte; James T. Peterson (Ecological Modelling, 2024)

Prototyping structured decision making for water resource management in the San Francisco Bay-Delta - James T. Peterson; Erin McCreless; Adam Duarte; Patti Wohner; Scott Hamilton; Josue Medellín-Azuara; Alvar Escriva-Bou (Environmental Science & Policy, 2024)

Volatile fatty acid and methane production from vinasse and microalgae using two-stage anaerobic co-digestion - Agnes Adam Duarte Pinheiro; Edilberto Mariano da Silva; Dicla Cesario Pereira de Oliveira; Bruna Scandolara Magnus; Fabrício Motteran; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Environmental Science and Pollution Research, 2024)

Diagnostic performance, stability, and acceptability of self-collected saliva without additives for SARS-CoV-2 molecular diagnosis - Catalina Marín-Echeverri; Lizet Pérez-Zapata; Laura Álvarez-Acevedo; Sebastián Gutiérrez-Hincapié; Melissa Adams-Parra; Didier Tirado-Duarte; Johan Bolívar-Muñoz; Marlon Gallego-Gómez; Yadira Galeano-Castañeda; Christian Piedrahita-Ochoa; Heiddy del Valle Arrieta (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Anaerobic co-digestion of microalgal biomass, sugarcane vinasse, and residual glycerol from biodiesel using simplex-centroid mixture design: methane potential, synergic effect, and microbial diversity - Edilberto Mariano da Silva; Sayonara Costa de Araújo; Shyrlane Torres Soares Veras; Agnes Adam Duarte Pinheiro; Fabrício Motteran; Mario Takayuki Kato; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Environmental Science and Pollution Research, 2024)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

An evaluation of multistate occupancy models for estimating relative abundance and population trends - Valerie A. Steen; Adam Duarte; James T. Peterson (Ecological Modelling, 2023)

Editorial: Emerging Topics in Coastal and Transitional Ecosystems: Science, Literacy, and Innovation - Bernardo Duarte; Célia M. Teixeira; Irene Martins; Aschwin H. Engelen; Raquel L. Costa; Janine Barbara Adams; Maria João Bebianno; Ricardo A. Melo; Vanessa F. Fonseca (Frontiers in Marine Science, 2022)

Invasion and Extirpation Potential of Native and Invasive Spartina Species Under Climate Change - Francisco O. Borges; Catarina P. Santos; José R. Paula; Enrique Mateos-Naranjo; Susana Redondo-Gomez; Janine Barbara Adams; Isabel Caçador; Vanessa F. Fonseca; Patrick Reis-Santos; Bernardo Duarte; Rui Rosa (Frontiers in Marine Science, 2021)
Coastal areas host some of the planet’s most productive ecosystems, providing life-sustaining ecological services and several benefits to humankind, while also being some of the most threatened areas (e.g., by globalization, climate change, and biological invasion). Salt marshes are coastal habitats with a key role in food and shelter provisioning, sediment deposition, nutrient cycling and carbon storage. Spartina spp. is a genus of grass halophytes which occurs in salt marshes worldwide, and includes species with different invasive potential. We evaluated the effect of climate change in the distribution and invasion potential of five Spartina species ( S. anglica , S. alterniflora , S. densiflora , S. patens , and S. maritima ) at a global scale. Species distribution models (SDMs) were applied on species occurrence data and atmospheric environmental predictors (WorldClim 2.1) to project potential changes in habitat suitability and associated changes in distribution and species co-occurrence until the end of the century, across four Shared Socioeconomic Pathway scenarios (i.e., SSP1-2.6 to SSP5-8.5). Projections showed a global trend for increasing species co-occurrence, with a general range expansion potentiated by increasing pathway severity. This study suggests that Spartina species can potentially benefit from climate change, predicting poleward expansions in the Northern Hemisphere for most species, with results pointing at increased conflict and invasion potential in Northern Europe and East Asian shorelines, already under strong invasive pressure. S. anglica is projected to remain a successful invader, with more severe scenarios likely favoring greater expansions. S. alterniflora exhibits very low expansion comparatively, despite exhibiting the same northward distribution shift. SSP1-2.6 produced the smallest change to species co-occurrence, suggesting a smaller potential for invasion-related conflicts, although still registering a potential net expansion for the Genus. Despite their limitations, SDMs can help establish general trends in climate change ecology and inform policymakers and environmental agents to ensure the correct management of these habitats and, ultimately, ecosystems.

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Gustavo A. S. Duarte; Helena D. M. Villela; Matheus Deocleciano; Denise Silva; Adam Barno; Pedro M. Cardoso; Caren L. S. Vilela; Phillipe Rosado; Camila S. M. A. Messias; Maria Alejandra Chacon; Erika P. Santoro; Daniele B. Olmedo; et al. (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Habitat monitoring and genotoxicity in Ucides cordatus (Crustacea: Ucididae), as tools to manage a mangrove reserve in southeastern Brazil - M. A. A. Pinheiro; L. F. A. Duarte; T. R. Toledo; M. L. Adam; R. A. Torres (Environmental Monitoring and Assessment, 2013)

Range expansion of nonindigenous caribou in the Aleutian archipelago of Alaska - Mark A. Ricca; Floyd W. Weckerly; Adam Duarte; Jeffrey C. Williams (Biological Invasions, 2012)

Does rumen–reticulum capacity correlate with body size or age in black-tailed deer? - Adam Duarte; Dale R. McCullough; Floyd W. Weckerly (European Journal of Wildlife Research, 2011)

Rejoinder to: Influence of river discharge in the tropical and subtropical North Atlantic Ocean - Antonio Tovar-Sanchez; Carlos M. Duarte; Adam B. Kustka; Susana Agustí; Jordi Dachs; David A. Hutchins; Douglas G. Capone; Sergio A. Sañudo-Wilhelmy (Limnology and Oceanography, 2009)

Effects of dust deposition and river discharges on trace metal composition of Trichodesmium spp. in the tropical and subtropical North Atlantic Ocean - Antonio Tovar-Sanchez; Sergio A. Sañudo-Wilhelmy; Adam B. Kustka; Susana Agustí; Jordi Dachs; David A. Hutchins; Douglas G. Capone; Carlos M. Duarte (Limnology and Oceanography, 2006)
We present the elemental composition (Al, Cd, Co, Cu, Fe, Mn, Mo, Ni, V, Zn, and P) of field‐collected Trichodesmium populations. To distinguish the effects of river discharges (Amazon and Niger Rivers) and Saharan dust deposition on metal concentrations in the colonies, samples were collected both in the western (February 2001, July‐August 2001, and April‐May 2003) and eastern (May‐June 2003) basins of the North Atlantic. Metal composition (medians normalized to P) in Trichodesmium ranged from 0.011 mmol mol −1 for Co to 39 mmol mol −1 for Fe and varied over an order of magnitude among different locations. A comparison of metal ratios measured in the Trichodesmium colonies with ratios reported for the potential sources suggests that the most important sources of trace metals to the tropical and subtropical Atlantic during our sampling were the Amazon and Niger Rivers, rather than dust deposition from the Sahara.